ANTI-CORROSION PROTECTION OF PIPELINES - Martyniuk, R. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
Currently, in our country, the issue of protecting metals from corrosion has achieved high results, so there is a big gap between the achievements of scientific research in this direction and their use in industry. It is necessary to develop and implement highly effective methods of increasing the strength, corrosion resistance, heat and cold resistance of metals and alloys. Popularization, dissemination and implementation of effective methods of protection against corrosion and corrosive-mechanical destruction of machines, devices, equipment and metal structures are of great importance. During surface-plastic deformation, a chip is not formed, but a fine plastic deformation of the surface layer takes place. As a result, the surface layer is strengthened, wear resistance and resistance to corrosive environment increases. In many cases, the use of surface-plastic deformation makes it possible to increase the safety margin of parts working under variable loads by 1.5 to 3 times, and to increase the service life of parts. The paper examines directions for increasing the stability of parts of oil industry equipment by the method of surface plastic deformation, for resistance against various types of corrosion and corrosive-mechanical destruction. Fatigue is the phenomenon of gradual accumulation of material damage under the action of variable loads, which leads to changes in the properties of crack formation, their development and destruction. The processes of metal fatigue have been studied by many researchers, many hypotheses have been put forward, but the nature of fatigue remains largely unexplained.